PENGARUH KOMPENSASI DAN MOTIVASI SERTA DISIPLIN TERHADAP KINERJA KARYAWAN PADA KOPERASI SERBA USAHA BUMI MANGUPURA SEJAHTERA BADUNG - Putra Mahardika, I Gusti Ngurah Agung; Ardana, Komang (E-Jurnal Manajemen; Vol 2 No 11 (2013), 2013)
Employees’ performances are the output of quality and quantity that can be achieved by an employee in accomplished the job which is compatible with something that is charged to the employee. In order to get high performance of employees, the company has to be aware about the factors that influence employees’ performance. The purpose of research is identifying the compensation, motivation, and discipline on employees’ performance either simultaneously and partially. This research is conducted in Bumi Mangupura Sejahtera Badung’s multi purpose cooperative that uses all of employees as the respondents. The numbers of respondents in this research are 32 people. Collecting of data is conducted by questionnaire, interview, and observation. Technique of analyzing data is conducted by best linear unbiased estimator, F test, t test, and standardize coefficient beta. Regarding to result of study, it is known that the compensation, motivation, and discipline simultaneously affect employees’ performance significantly. Compensation, motivation, and discipline have good affects on employees’ performance partially and significantly and compensation as independent variable that affect dominantly on employees’ performance. From the management’s discovery research, Bumi Mangupura sejahtera multi purpose cooperative is expected to give more attention on aspect in giving allowance and incentive. On Bumi Mangupura Sejahtera multi purpose cooperative management’s side is also expected to trigger eagerness of employees. On discipline enforcement’s side, it needs to be improved the supervision to make them do more commitment. Key words : compensation, motivation, discipline, performance.
Keywords: kompensasi, motivasi, disiplin, kinerja